(untitled) (Al-Academy, 2023)
The artistic process operates whether in general in all arts or specifically in one type of arts or one of the genres of arts types on the preoccupations of the pressing artistic references as the founder of the artistic work in the material formulations on the one hand and on the other hand as a translator to understand the artistic achievement in general and plastic art in particular and for the importance The researcher chose the title of her research tagged (the preoccupations of the pressing reference and its impact on the formations of postmodern arts).The first chapter of the methodological framework deals with the problem of research, importance, objective, limits, and then terminology and its definition, and then the second chapter, which consisted of two chapters in the concept of the pressing technical references, and the second chapter dealt with the aesthetic preoccupations of the pressing technical references in the artistic achievement, and then the indicators of the theoretical framework, and then the research procedures that formed the third chapter With the analysis of the sample, and then the fourth chapter, the results and conclusions, and the most important results were: The reference system in general, and the pressing artistic reference, in particular, works to generate a different artistic achievement on the aesthetic and intellectual level, and the functional and intellectual preoccupations as an expressive aesthetic value for the artwork.The most important conclusions: The expressive power as an intellectual value linked to the form is determined by the pressing artistic references as the mediator responsible for translating ideas from the invisible in the imagination of the artist to the visible in the material medium and then to the invisible in the mind of the recipient. And then the sources